First-principles investigation of alkali-metal adsorption in nitrogen/oxygen doped borophenes - Yadav V.K.; Saroj A.; Mishra B.K.; Ramanathan V. (My University, 2025)
Recently fabricated borophene sheets have garnered significant attention due to their exceptional stability and unique electronic properties, making them promising for sensing and energy storage applications. This study employs first-principles calculations to investigate nitrogen and oxygen-doped two-dimensional borophene sheets of mixed three- and six-membered rings. Adsorption configurations, energies, and electronic properties of metal atoms on doped borophene were explored to reveal their interaction mechanisms. Our findings show that nitrogen doping enhances borophene's stability, with nitrogen-doped monolayers showing the highest adsorption energies for lithium (-3.434 eV) and sodium (-2.281 eV), outperforming non-doped and oxygen-doped borophene. Additionally, oxygen-doped bilayers exhibit strong intercalation energies for lithium (-4.616 eV) and sodium (-3.170 eV). Nitrogen/oxygen-doped borophene increases the carrier concentration and shortens the phonon mean free paths, reducing thermal conductivity. Ab initio molecular dynamics simulations confirm the stability of these doped borophenes at 300 K, reinforcing their potential for advanced applications. © 2025 Elsevier B.V.